An Empirical Estimation of the Value-Added Impact of Lucca Comics and Games Festival on Hotel Performance. (March 2020) - Capocchi, Alessandro; Barboza, Gustavo; DeMicco, Fred; Vallone, Cinzia
Our study aims at investigating how the "Lucca Comics & Games Festival" has grown to become a major revenue generator for the hotel industry and the overall Lucca economic activity. Our study placed a specific interest in analyzing, estimating, and approximating the monetary impact of "Lucca Comics & Games Festival" on the hotel and hospitality segment, and provided extensions to the larger economic activity of the Lucca economy. Our article is an empirical paper, and as such we do not claim to make significant theoretical contributions in terms of model development. Instead, we provide a useful set of tools to estimate and assess the value added of the festival on the economic performance of the hotel sector in the city of Lucca. The article makes a clear contribution to the knowledge related to experiential creation in the field of tourism. Particularly, we provide a simple methodology that allows us to estimate a value-added impact measure.